The longitudinal relationship between post-traumatic stress disorder and perceived social support in survivors of traumatic injury. Issue 1 (27th September 2016) - Nickerson, A.; Creamer, M.; Forbes, D.; McFarlane, A. C.; O'Donnell, M. L.; Silove, D.; Steel, Z.; Felmingham, K.; Hadzi-Pavlovic, D.; Bryant, R. A.
Abstract : Background: Although perceived social support is thought to be a strong predictor of psychological outcomes following trauma exposure, the temporal relationship between perceived positive and negative social support and post-traumatic stress disorder (PTSD) symptoms has not been empirically established. This study investigated the temporal sequencing of perceived positive social support, perceived negative social support, and PTSD symptoms in the 6 years following trauma exposure among survivors of traumatic injury. Method: Participants were 1132 trauma survivors initially assessed upon admission to one of four Level 1 trauma hospitals in Australia after experiencing a traumatic injury. Participants were followed up at 3 months, 12 months, 24 months, and 6 years after the traumatic event. Results: Latent difference score analyses revealed that greater severity of PTSD symptoms predicted subsequent increases in perceived negative social support at each time-point. Greater severity of PTSD symptoms predicted subsequent decreases in perceived positive social support between 3 and 12 months. High levels of perceived positive or negative social support did not predict subsequent changes in PTSD symptoms at any time-point. Conclusions: Results highlight the impact of PTSD symptoms on subsequent perceived social support, regardless of the type of support provided. The finding that perceived social support does not influence subsequent PTSD symptoms is novel, and indicates that the relationship between PTSD and perceived social support may be unidirectional.